Low Density Granulocytes and Dysregulated Neutrophils Driving Autoinflammatory Manifestations in NEMO Deficiency - ÖZEN, AHMET OĞUZHAN; YÜCELTEN, AYŞE DENİZ; AYDINER, ELİF; TRUE, ÖMER; BARIŞ, SAFA; CİNEL, ZELİHA LEYLA (SPRINGER/PLENUM PUBLISHERS, 2022)
NF-kappa B essential modulator (NEMO, IKK-gamma) deficiency is a rare combined immunodeficiency caused by mutations in the IKBKG gene. Conventionally, patients are afflicted with life threatening recurrent microbial infections. Paradoxically, the spectrum of clinical manifestations includes severe inflammatory disorders. The mechanisms leading to autoinflammation in NEMO deficiency are currently unknown. Herein, we sought to investigate the underlying mechanisms of clinical autoinflammatory manifestations in a 12-years old male NEMO deficiency (EDA-ID, OMIM #300,291) patient by comparing the immune profile of the patient before and after hematopoietic stem cell transplantation (HSCT). Response to NF-kB activators were measured by cytokine ELISA. Neutrophil and low-density granulocyte (LDG) populations were analyzed by flow cytometry. Peripheral blood mononuclear cells (PBMC) transcriptome before and after HSCT and transcriptome of sorted normal-density neutrophils and LDGs were determined using the NanoString nCounter gene expression panels. ISG15 expression and protein ISGylation was based on Immunoblotting. Consistent with the immune deficiency, PBMCs of the patient were unresponsive to toll-like and T cell receptor-activators. Paradoxically, LDGs comprised 35% of patient PBMCs and elevated expression of genes such as MMP9, LTF, and LCN2 in the granulocytic lineage, high levels of IP-10 in the patient's plasma, spontaneous ISG15 expression and protein ISGylation indicative of a spontaneous type I interferon (IFN) signature were observed, all of which normalized after HSCT. Collectively, our results suggest that type I IFN signature observed in the patient, dysregulated LDGs and spontaneously activated neutrophils, potentially contribute to tissue damage in NEMO deficiency.
Keywords: NEMO deficiency; Autoinflammation; Low-density granulocytes; Neutrophil activation related genes; Interferon stimulated genes (ISGs); NF-KAPPA-B; SYSTEMIC-LUPUS-ERYTHEMATOSUS; ECTODERMAL DYSPLASIA; INCONTINENTIA PIGMENTI; CATHEPSIN-G; IKK-GAMMA; T-CELLS; IMMUNODEFICIENCY; ACTIVATION; MUTATION